Semantics of Tengrianism in K. Montakhayev’s graphic works - Mazina, Yulia; Serbina, Marina; Smailov, Zarykhan (project baikal, 2025)
The article considers the influence of Tengrianism on the graphic works of artist Kaldybai Montakhayev. Tengrianism is considered as a cultural code of nomadic culture, which is widely spread on the territory of Kazakhstan. The code influences the formation of succession principles. Through the works of artist K. Montakhaev the authors consider the sense-forming factors of Tengrianism, identify and typify the archetypes and symbols that permeate this culture.